The Great Recession and Children's Mental Health in Australia - Melisa Bubonya; Deborah A. Cobb-Clark; Daniel Christensen; Sarah E. Johnson; Stephen R. Zubrick (Institute of Labor Economics (IZA), 2018)
This paper analyzes the effects of 'shocks' to community-level unemployment expectations, induced by the onset of the Great Recession, on children's mental well-being. The Australian experience of the Great Recession represents a unique case study as despite little change in actual unemployment rates, levels of economic uncertainty grew. This affords us the ability to examine the effects of shocks to economic expectations independent of any actual changes to economic conditions. We draw on and link data from multiple sources, including a longitudinal cohort study of children, a consumer sentiment survey and data on local economic conditions. Using our purpose-built data set, we estimate difference-in-differences models to identify plausibly causal effects. We find, for boys, there is no detectable effect of community-level unemployment expectations shocks on mental health. For girls, however, there are modest increases in mental health problems and externalizing behaviors, as measured by the Strengths and Difficulties Questionnaire. We additionally find no discernable change in mother's psychological distress as a result of expectations shocks. These results are stable after controlling for actual labor market conditions.
Keywords: I31; G01; D84; 330; mental health; children; Great Recession; unemployment expectations; cohort studies